Perspektif Perbandingan: Kondisi Sosial, Ekonomi, dan Pemerintahan Indonesia dan Iran - Natalis Christian; Arlina Arlina; Julie Tryany; Vera Laurence Liang; Yohanis Rerung (LPPM Universitas Sains dan Teknologi Komputer, 2024)
This research compares the social, economic and governmental conditions of Indonesia and Iran. Socially, Indonesia and Iran face challenges in maintaining social harmony amidst diversity. Economically, Indonesia is bigger and more advanced than Iran, but both countries experience economic disparities and infrastructure problems. International sanctions are impacting Iran's economy while Indonesia continues to strive to become more competitive in the global market. From a political perspective, Indonesia is a representative democracy, while Iran is an Islamic republic whose highest power is held by a spiritual leader. However, corruption and demands for political reform remain challenges in both countries. Despite significant differences, both countries have similar challenges in terms of maintaining stability, overcoming inequality and improving governance. This study provides valuable insight into social, economic and political trends in Indonesia and Iran that can be used to develop more effective policies to improve people's welfare and strengthen government systems.